Health education and Nigerian national development in this millennium (2007)
This paper discussed Health education as one of the means of achieving the Millennium Development Goals in Nigeria. Health education is a basic right and the most effective means of preventing disabling conditions and diseases that might cripple the entire workforce in the nation. Indeed, the country will reduce the amount spent on sensitization programmes mounted for different diseases like HIV/AIDS, malaria cancer etc. where health education exists and is made a core subject at all levels of education (kindergarten, primary, secondary/ and tertiary). It is recommended among others that health education should remain a single separate subject in both primary and secondary schools and tertiary institutions, and should be an examinable subject at senior secondary level.